Terminology for Librarian Help on the Home Page - Matthews, Leni (Evidence Based Library and Information Practice, 2018)
A usability study was run to validate terminology (labels) for seeking librarians from the UTA Libraries homepage. Seven new labels were proposed by librarians. They hoped these labels would help users in finding them and discovering librarians various skills to meet users' needs. Students were presented with a paper prototype of the library's homepage that included the seven proposed labels. They were asked to find information using two search goals as it related to seeking assistance from a librarian.